Peran Dewan Kehormatan dalam Perspektif Pembinaan dan Pengawasan Notaris - Fransisca, Lydia (Notary Journal, 2025)
Notary is a professional in the legal field playing an important role in creating legal certainty and assisting the public in various civil legal matters. In carrying out their duties, notary must adhere strictly to the notary's code of ethics, which constitutes all its moral principles. In practice, notaries are supervised by an honorary council. This supervision is very necessary so that notaries do not ignore the nobility and dignity of their profession. The code of ethics is not just a set of rules or guidelines for behavior, but reflects the essence of the integrity and responsibility of a notary as a professional. Therefore, it is important for notaries to understand and adhere to their code of ethics seriously. This research aims to determine the role of the Honorary Council in supervising and enforcing the notary’s code of ethics, as well as its role in enforcing ethics. This study is a normative legal research with descriptive research type. The approach used is normative approach. Based on the results of this research, it is known that the Code of Ethics is a guideline that not only sets standards of behavior, but also maintains the integrity, honesty, and professionalism of notaries. Then, to prevent ethical violations, the Honorary Council needs to improve supervision, education and training for notaries, transparency, accountability and coordination between ethical institutions in this case the Honorary Council and the Notary Supervisory Board to realize dignified notaries. Bahasa Indonesia Abstract: Notaris adalah seorang profesional di bidang hukum yang berperan penting dalam menciptakan kepastian hukum dan membantu masyarakat dalam berbagai urusan hukum keperdataan. Notaris dalam menjalankan tugasnya harus berpegang teguh pada kode etik Notaris yang merupakan seluruh kaedah moralnya. Dalam praktiknya Notaris diawasi oleh Dewan Kehormatan Notaris. Pengawasan ini sangat diperlukan agar Notaris tidak mengabaikan keluhuran dan martabat profesinya. Kode etik bukan hanya sekadar seperangkat aturan atau pedoman perilaku, tetapi mencerminkan esensi dari integritas dan tanggung jawab notaris sebagai seorang profesional. Oleh karena itu, penting bagi notaris untuk memahami dan mematuhi kode etik mereka dengan sungguh-sungguh. Penelitian ini bertujuan untuk mengetahui peran Dewan Kehormatan dalam mengawasi dan menegakkan kode etik notaris, serta perannya dalam penegakkan etik. Penelitian ini adalah penelitian hukum normatif dengan tipe penelitian deskriptif. Pendekatan masalah yang digunakan adalah pendekatan normatif. Berdasarkan hasil penelitian ini, diketahui bahwa Kode Etik merupakan pedoman yang tidak hanya menetapkan standar perilaku, tetapi juga menjaga integritas, kejujuran, dan profesionalisme notaris. Kemudian, untuk mencegah pelanggaran etik, Dewan Kehormatan perlu meningkatkan pengawasan, pendidikan dan pelatihan bagi notaris, transparansi, akuntabilitas dan koordinasi antara lembaga etik dalam hal ini Dewan Kehormatan dengan Majelis Pengawas Notaris untuk mewujudkan notaris bermartabat.